Using visual cues of microhabitat traits to find home: the case study of a bromeliad-living jumping spider (Salticidae) - de Omena, Paula M. [UNESP]; Romero, Gustavo Q. [UNESP] (Oxford University Press, 2010)
There are many examples of predators having specialized microhabitat requirements, but the sensory mechanisms by which predators detect, identify, and evaluate microhabitats are only poorly understood. The ability to use visual cues to select microhabitats was investigated using Psecas chapoda, a bromeliad-dwelling salticid spider. In this study, we manipulated real plants and photos of plants to test whether P. chapoda uses plant architecture to select host plants and whether visual cues alone are sufficient for them to select microhabitats. The use of photos on the experiment allowed us to exclude the potential influence of other cues, such as color and odor, on host plant selection by the spider. Our results showed that P. chapoda selects their microhabitat by evaluating architectural features of leaves and rosette of the host plants. Rosette-shaped plants (Agavaceae) were preferred over other types of plant architecture. Spiders showed a preference for photographs of rosette-shaped plants having narrow and long leaves, confirming that they can make these choices entirely on the basis of vision. These salticids can recognize and select microhabitats bearing specific architectural features, which possibly reflects an adaptation to choose microhabitats that are favorable to its survivorship.
Keywords: Bromeliaceae; Host plant selection; Plant architecture; Visual cues; visual selection; Salticidae